Pendidikan Karakter Melalui Ekstrakurikuler Pencinta Alam di SMK Negeri 1 Bawen (Department of Physical Education, Sport, Health and Recreation, 2017)
The purpose of this study is to find the implementation of character education and the value of a character students got through extracurricular nature lovers in state vocational schools 1 bawen.metode used is the method descriptive .Objects in peneiltian this is character education and the value of a character .The result of this research is the implementation of character education through extracurricular nature lovers in state vocational schools 1 bawen includes three method , the first is keteladanan applied in the form of a briefing directly and the provision of example .A method of the second is learning applied in the form of training , the experience and the punishment .A method of the third one is empowerment and pembudayaan applied in the form of task and cogitation .The research character education through extracurricular nature lovers in state vocational schools 1 bawen it can be said high . This was strengthened through the result of reckoning descriptive prosentase namely the attitudes and behavior in conjunction with the lord 77 % , the attitudes and behavior in conjunction with oneself 67 % , the attitudes and behavior in its relationship to society and the people of 63 % , as well as the attitudes and behavior in its relation to the natural world around reached 83 % .Advice to the tutors to get more increase the supervision of activity that is performed by students .To the head of greenpeace should be firmer in decision-making by mutual agreement , further improve communication among members .